FORMING NATION CHARACTERS THROUGH HISTORY LEARNING PROCESS - Yusuf Budi Prasetya Santosa; Arief Hidayat (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2021)
Learning is not just a process of transfer of knowledge (transfer of knowledge) from teachers to students, but also a process of transfer of values. This means that the learning process, apart from being a process of transmitting knowledge with cognitive goals, also deals with the process of developing and building the character of students. Historical learning has a strategic role in shaping the character of the nation. A good history study does not only emphasize cognitive aspects but also must pay attention to affective and psychomotor aspects. The history learning process must be able to explore noble historical values ​​from each historical event that is learned, from which the students can learn from these values ​​and use them for their future lives. So, later there will be historical awareness in students. The exploration of noble values ​​and the emergence of historical awareness can be obtained by using the appropriate historical learning method. The learning model has a strategic function in the process of learning history. Four learning models can trigger curiosity, creativity, and critical thinking of students, including discovery-based learning, problem-based learning, project-based learning, and the information processing models. Keywords: students, history learning, historical awareness, national character